Mental healthcare provider’s perceptions on the effectiveness and viability of telepsychiatry in Allegheny County Jail. - Tiffany Habib (The Young Researcher, 2023)
Prior research has considered the lack of mental healthcare services offered to the inmates in Pennsylvania, Allegheny County Jail. However, there is limited research on how telepsychiatry impacts the mental health services provided in this jail, leading to the question: What are local mental healthcare workers’ opinions on the effectiveness and viability of telepsychiatry in Allegheny County jail? The researcher used a convergent parallel, mixed method Google Forms survey to obtain this data. This study found that while most providers preferred in-person care over telepsychiatry, they conceded that this system can be beneficial for the inmates at this local jail. Providers’ willingness to work with the jail also increased when using this system. These findings demonstrate that using telepsychiatry within Allegheny County Jail is necessary because it could alleviate the severe understaffing and lack of mental health services in not only this local jail, but jails across the nation.